Education in Values – in the Centre of Axiological Dilemmas of the Contemporary Education - Olbrycht, Katarzyna (Paedagogia Christiana, 2012)
The author presents an argument that education in values is in the centre of axiological dilemmas of the contemporary education. She begins with introducing the main meanings of the term education and explaining how education in values is understood. The second part of the article consists of an analysis of contemporary dilemmas associated with education in values, especially how difficult it is to reconcile educating and upbringing in pragmatic and consumer values with higher, pro-development values. The next part discusses the educational path of assimilating values (preparation for discovery, reliving, interiorization, internalization). Finally, the text points out the dilemmas associated with education in personal values, in the light of Christian education.